Petrographic Variations in the Deccan Basalt Lava Flows of Rajura Volcanics, central India: Textural Implications - Deshmukh, M. S. (Journal of Scientific Research, 2024)
The present study encompasses petrographic variations in simple Deccan basaltic lava flows of the Rajura volcanics, central India. The Deccan basalt lava flows entirely covered the area and exposed in the form of moderate hillocks. During geological fieldwork, flows are identified and differentiated based on mineral content, relative grain size, presence of phenocrysts, and red bole horizons. Flow mapping reveals three basalt lava flows: mafic plagioclase microphyric basalt, phyric basalt, and plagioclase mafic microphyric basalt. The petrographic study of the lava flows was carried out to understand the mineralogy, textural patterns, crystallization, and genetic significance of the lava flows. The result indicates dominant plagioclase and clinopyroxene minerals with opaques exhibit porphyritic, glameroporphyritic, ophitic, and sub-ophitic textures. The petrographic variations are due to the combination of several factors like gravitational sinking of phenocryst, low viscosity, and slow rate of effusion of lava flows, as described by earlier workers. Plagioclase occurs as phenocrysts and in the groundmass phase, indicating early crystallization of phenocryst followed by crystallization of groundmass. The petrographic studies are further useful to correlate the lava flows exposed in different hillocks of the area.